Aesthetics, applications, artistry and anarchy : essays in prehistoric and contemporary art : a festschrift in honour of John Kay Clegg, 11 January 1935 - 1 March 2015 - Clegg, John, 1935-2015,; Huntley, Jillian,; Nash, George, (Archaeopress Publishing Ltd, 2019)
This volume, in honour of John Kay Clegg, consists of papers by rock art researchers from around the world on topics such as aesthetics, the application of statistical analyses, frontier conflict and layered symbolic meanings, the deliberate use of optical illusion, and the contemporary significance of ancient and street art.